The prevalence and drivers of early marriage across three generations in three districts from Amhara, Oromia and Southern Nations, Nationalities and Peoples regions of Ethiopia - Melese Getu; Guday Emirie; Kassahun Habtamu (Ethiopian Journal of the Social Sciences and Humanities, 2021)
Early marriage is a harmful traditional practice which affects millions of children worldwide. In the developing world, one in three will marry by the age of 18 and one in nine will marry by the age of 15. This article presents the findings of a study which established the prevalence and drivers of early marriage in Alefa, Diksis and Gorche districts of the Amhara, Oromia and Southern Nations, Nationalities and Peoples (SNNP) regions, respectively. A cross-sectional survey research design was employed. A total of 1199 women participated in a quantitative survey and data were analysed using descriptive and inferential statistics. The prevalence of early marriage among respondents was found to be 69.9%. The overall mean age at first marriage of respondents was found to be 14.8. An overall declining trend in the prevalence of early marriage and increasing trend in mean age at first marriage were noted. Respondents attendance of formal school, whether or not fathers ever attended formal school and size of land of natal family were found to be the variables significantly associated with respondents’ age at first marriage. The drivers of early marriage were categorized into gendered social norms, economic contexts, and institutional factors. Some conclusions are drawn based on the research findings.